PENINGKATAN KOMPETENSI KEPALA MADRASAH DALAM MENYIAPKAN DOKUMEN AKREDITASI MADRASAH IASP 2020 MELALUI PEMBIMBINGAN INTENSIF TERPROGRAM (PINTER) DI MA NU GESI KABUPATEN SRAGEN - AMIN SARWATI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This best practice was carried out at MA Nahdlatul Ulama Gesi, Sragen Regency as the MA target for piloting the implementation of the 2020 IASP madrasa accreditation in September-October 2020 by involving madrasa heads, teachers and education staff. This best practice uses a qualitative approach without using cycles. The objectives of this best practice are to determine: 1) the competence of the Madrasah Head in preparing the 2020 IASP Madrasah accreditation document at MA NU Gesi, Sragen Regency; 2) the implementation of Programmed Intensive Guidance (PINTER) in improving the competence of Madrasah Heads preparing the IASP 2020 Madrasah accreditation document for MA NU Gesi, Sragen Regency; 3) the results of the implementation of Programmed Intensive Guidance (PINTER) in improving the competence of Madrasah Heads preparing the IASP 2020 madrasa accreditation document at MA NU Gesi, Sragen Regency. The results obtained, when the initial condition of the Madrasah Head's competence in preparing the IASP 2020 madrasa accreditation document was still low, after the madrasa supervisor as the supervisor carried out Programmed Intensive Guidance (PINTER) showed a significant increase, namely 96% of the 2020 IASP madrasa accreditation documents that had to be prepared. fulfilled. As a suggestion regarding best practice research, it only focuses on providing and fulfilling supporting documents for IASP 2020 madrasah accreditation, so research can be followed up with a focus on other aspects of preparation, such as simulation of the implementation of online mode visitations and other aspects that are still closely related to the preparation for madrasa accreditation implementation. IASP 2020. ABSTRAKBest practice ini dilaksanakan di MA Nahdlatul Ulama Gesi Kabupaten Sragen sebagai MA sasaran piloting pelaksanaan akreditasi madrasah IASP 2020 pada bulan September- Oktober 2020 dengan melibatkan kepala madrasah, guru dan tenaga kependidikan.Best practice ini menggunakan pendekatan kualitatif tanpa menggunakan siklus. Tujuan best practice ini adalah untuk mengetahui: 1) kompetensi Kepala Madrasah dalam menyiapkan dokumen akreditasi madrasah IASP 2020 di MA NU Gesi Kabupaten Sragen; 2) pelaksanaan Pembimbingan Intensif Terprogram (PINTER) dalam meningkatkan kompetensi Kepala Madrasah menyiapkan dokumen akreditasi madrasah IASP 2020 MA NU Gesi Kabupaten Sragen; 3) hasil pelaksanaan Pembimbingan Intensif Terprogram (PINTER) dalam meningkatkan kompetensi Kepala Madrasah menyiapkan dokumen akreditasi madrasah IASP 2020 di MA NU Gesi Kabupaten Sragen. Hasil penelitian yang diperoleh, pada saat kondisi awal kompetensi Kepala Madrasah dalam mempersiapkan dokumen akreditasi madrasah IASP 2020 masih rendah, setelah pengawas madrasah selaku pembina melaksanakan  Pembimbingan Intensif Terprogram (PINTER) menunjukkan peningkatan yang signifikan  yaitu 96% dokumen akreditasi madrasah IASP 2020 yang harus dipersiapkan  dapat terpenuhi. Sebagai saran sehubungan penelitian best practice ini hanya terfokus pada penyediaan dan pemenuhan dokumen pendukung akreditasi madrasah IASP 2020, maka dapat ditindaklanjuti penelitian dengan fokus pada aspek persiapan yang lain, seperti simulasi pelaksanaan visitasi moda daring dan aspek lain yang masih terkait erat dengan persiapan pelaksanaan akreditasi madrasah IASP 2020.